PREVENTION AND MANAGEMENT OF SYSTEMIC COMPLICATIONS ARISING FROM POOR ORAL HYGIENE: CURRENT STATE OF KNOWLEDGE - Katarzyna Nycz; Jędrzej Sztajura (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Oral health is increasingly recognized as a critical component of overall health and well-being. Poor oral hygiene, particularly dental caries and periodontal disease, has been linked not only to local oral conditions but also to systemic complications, including cardiovascular disease, type 2 diabetes mellitus, respiratory infections, adverse pregnancy outcomes, and neurodegenerative disorders. This review aims to provide a comprehensive overview of the prevention and management of systemic complications arising from poor oral hygiene, summarizing current evidence on biological mechanisms, disease associations, and preventive strategies. Materials and Methods: A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar to identify studies investigating the relationship between oral hygiene, periodontal disease, and systemic health outcomes. Keywords included: oral hygiene, periodontal disease, systemic diseases, cardiovascular disease, diabetes, adverse pregnancy outcomes, respiratory disease, neurodegenerative disease, and oral-systemic link. Conclusion: Evidence indicates that oral health is essential for maintaining physical, mental, and social well-being. Preventive dental care, including early detection and management of caries, periodontal disease, and malocclusion, reduces disease progression, systemic complications, and psychosocial burden. Equitable access to dental services is critical, as limited access exacerbates health disparities and worsens outcomes. Integrating oral healthcare within comprehensive health systems and emphasizing prevention can improve individual and population-level health and quality of life.